O centro principal de João Pessoa: espacialidade, historicidade e centralidades. - Sales, Andréa Leandra Porto (2009)
The present study analyse the morphology and the dynamics of the main center of the city of João Pessoa, as well as the expressions of its centrality. This center stands out in intraurban structure as the place of higher concentration of tertiary activities, of better accessibility and greater symbolism. Articulates itself with all the other parts of intra-urban structure through its tentacles and set of tools that enable the flow of people, goods and information. Its centrality is revealed for what is in movement, before it, has various expressions that both quality and quantity materialized a morpho-functional structure that is its own and inherent to the process of (re) structuring of the city of João Pessoa. To limit the primate nucleus of the city this center acquired a mnemonic centrality, equally, multiple, complex and changing. To comprehend this center was necessary to go through the Western theories of production of urban space that deal with the issue of urban restructuring and central places, we adopt a variety of methodological procedures in order to respond as within the model of polycentric city and dispersed a central place to receive the name of principal.